Finding Nemo (The Original Magical Story, 2017)
When his son Nemo is captured by a diver in the Great Barrier Reef, Marlin stops at nothing to rescue him. Together with his new friend Dory, he sets off on a dangerous journey. Will they find Nemo against all odds? Enjoy a classic Disney Pixar experience with this magical storybook, Disney Pixar Finding Nemo The Original Magical Story.